2021
DOI: 10.3390/antiox10050720
|View full text |Cite
|
Sign up to set email alerts
|

Hidrox® and Endometriosis: Biochemical Evaluation of Oxidative Stress and Pain

Abstract: Endometriosis is a gynecological and painful condition affecting women of reproductive age. It is characterized by dysfunctional endometrium-like implants outside of the uterine cavity. The purpose of this study was to evaluate the effects of Hidrox®, an aqueous extract of olive pulp containing hydroxytyrosol, on endometriotic lesions associated with pro-oxidative alterations and pain-like behaviors. Endometriosis was induced by intraperitoneal injection of uterine fragments, and Hidrox® was administered daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 98 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…28 It has been hypothesized that eliminating oxidative stress may reduce the histopathological grade in endometrial implants and many studies have been conducted on this subject. 27,29,30 Proinflammatory cytokines such as IL-1, IL-6, IL-8, and TNF-α have also been shown to play a role in the pathology of endometriosis. 31 It has been demonstrated that there is an increase in TNF-α levels in the peritoneal fluids of women with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 It has been hypothesized that eliminating oxidative stress may reduce the histopathological grade in endometrial implants and many studies have been conducted on this subject. 27,29,30 Proinflammatory cytokines such as IL-1, IL-6, IL-8, and TNF-α have also been shown to play a role in the pathology of endometriosis. 31 It has been demonstrated that there is an increase in TNF-α levels in the peritoneal fluids of women with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ROS overproduction by microglia is suggested to be a main cause of neuronal damage and dysfunction inducing derangement of neuronal redox signaling circuits or direct oxidative damage [27,48]. Much evidence supports the role of oxidative stress in the progress of FM [5,49].…”
Section: Discussionmentioning
confidence: 99%
“…The dose and route of HD treatment were chosen based on previous studies [26][27][28]. At the end of the experiment, the L4-L6 region of the spinal cord from each rat was collected for all analyses.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…149). The formation of an immune oxidative environment within the hippocampus of endometriosis rats is one of the mechanisms leading to pain sensitisation, whereas the elevated oxidative state in the hippocampus was correlated with a lower level of BDNF (Refs 150, 151). Astrocytes and microglia are thought to be responsible for many inflammatory processes in affected brains, including secretion of inflammatory mediators and stimulation of the innate immune system (Ref.…”
Section: Altered Brain In Endometriosismentioning
confidence: 99%